Differentiation between Wines Originating from Different Red Wine Cultivars and Wine Regions by the Application of Stepwise Discriminant Analysis to Gas Chromatographic Data - Marais, J.; Van Rooyen, P. C.; Du Plessis, C. S. (South African Journal of Enology and Viticulture, 2017)
Stepwise discriminant analysis (SDA) was applied to gas chromatographic data of some volatile compounds extracted with freon from red wines. By means of this statistical method, Pinotage and Cabernet Sauvignon wines (1978 vintage) could be classified into separate groups, the most effective variables being hexanol and i-amyl acetate. Pinotage wines from three, and Cabernet Sauvignon wines from two localities (1979 vintage) were subjected to classification according to origin. Successful classifications were obtained using the variables ethyl acetate, ethyl caprate, i-amyl acetate as well as a compound tentatively identified as i-valeric acid.